Globalisation and media ethics in Africa - Isaac Phiri (Communicare)
The disintegration of military regimes and one-party rule occurring across Africa in the early 1990s allowed for the mushrooming of numerous new media initiatives and the resuscitation of hitherto dormant media operations. The enthusiasm was fuelled by promises of freedom of speech and prospects of the media becoming an autonomous fourth actor on the public stage. It was envisioned by many that the media would reject the ethos prevailing under hegemonic rule and adopt international norms. But nearly two decades later, media people and their organisations in sub-Saharan Africa are still entangled in a labyrinth of ethical dilemma. One of the big issues begging further research and reflection is whether to localise or globalise ethical discourse and practice. How far should indigenous cultural values inform journalism ethics? And, how can this be negotiated in a rapidly globalising environment? This paper uses the Zambian experience to advance the position that glocalisation - the hybridisation of ethical norms between the local and the global -provides the most enduring and acceptable foundation for ethical theorising and practice available to media professionals on the continent.